Tools for developers to manage their responsibilities introduced by agile software development - Avikainen, Petri (fi=Turun yliopisto|en=University of Turku|, 2016)
After the year 2001, when the Agile manifesto was published, the agile development principles have been largely adopted and are taken for granted in modern development process's. One of the most adopted of these principles is the Lean Software Development published in 2003. These principles are largely adopted from small start-ups to large global enterprises. One aspect that the agile methodologies introduce is large amount of practices and processes for developers to follow and handle. This rises the question of this study: Has the developers' responsibilities increased, and does it introduce new tools for developers to handle the responsibilities? The First Chapter introduces the transformation of software business to Agile development followed by the second Chapter where the main hypothesis is stated. Third Chapter studies the Lean Software Development and articulates the responsibilities introduced for the developers. Fourth Chapter presents the tools for handling these responsibilities and Fifth Chapter conducts a survey to verify these assumptions. The Chapter six concludes this thesis and rises possible future studies. In this study the Findings are that the Agile Development introduces responsibilities for developers, but it stays unclear if the amount has drastically increased.